COMPREHENSIVE STATISTICAL ASSESSMENT OF THE EFFECTS OF LIFESTYLE AND HEREDITARY FACTORS ON MEMORY AND VISUAL ACUITY (Multidisciplinary Journal of Science and Technology, 2026)
This article investigates and compares the effects of sleep duration, healthy nutrition, and time spent using smartphones on cognitive functions, particularly memory and attention, as well as on visual acuity in students and young professionals in the modern information environment, based on a questionnaire survey conducted among students. During the study, data were collected from 75 participants aged 19 to 39 using a specially developed Telegram bot and the Golovin chart.